Integrative analysis of multi-omics data for discovery of ferroptosis-related gene signature predicting immune activity in neuroblastoma - Hu, Jiajian; Song, Fengju; Kang, Wenjuan; Xia, Fantong; Song, Zi’an; Wang, Yangyang; Li, Jie; Zhao, Qiang (Frontiers in Pharmacology, 2023)
Immunotherapy for neuroblastoma remains unsatisfactory due to heterogeneity and weak immunogenicity. Exploring powerful signatures for the evaluation of immunotherapy outcomes remains the primary purpose. We constructed a ferroptosis related gene (FRG) signature by least absolute shrinkage and selection operator and Cox regression, identified 10 independent prognostic FRGs in training cohort (GSE62564), and then verified them in external validation cohort (TCGA). Associated with clinical factors, the signature accurately predicts overall survival of 3, 5, and 10 years. An independent prognostic nomogram including FRG risk, age, stage of the International Neuroblastoma Staging System, and MYCN status was constructed. The area under curves showed satisfactory prognostic predicting performance. Through bulk RNA-seq and proteomics data, we revealed the relationship between hub genes and the key onco-promoter MYCN gene and then validated the results in MYCN-amplified and MYCN-nonamplified cell lines with qRT-PCR. The FRG signature significantly divided patients into high- and low-risk groups; differentially expressed genes between the two groups were enriched in immune actions, autophagy and carcinogenesis behaviors. The low-risk group embodied higher positive immune component infiltration as well as higher expression of immune checkpoints with more favorable CYT (immune cytolytic activity). We verified the predictive power of this signature with data from melanoma patients undergoing immunotherapy, and the predictive power was satisfactory. Gene mutations were closely related to the signature and prognosis. AURKA and PRKAA2 were revealed to be nodal hub FRGs in the signature, and both were shown to have significantly different expressions between INSS IV stage and other stages after immunohistochemical validation. With single cell RNAseq analysis, we found that genes related to T cells were enriched in TNFA signaling and interferon-γ hallmark. In conclusion, we constructed a ferroptosis-related signature that can predict the outcomes and work in evaluating the effect of immunotherapy.